2007
DOI: 10.3171/jns.2007.106.5.907
|View full text |Cite
|
Sign up to set email alerts
|

Stent fracture and restenosis after placement of a drug-eluting device in the vertebral artery origin and treatment with the stent-in-stent technique

Abstract: The authors report two cases of stent fracture and restenosis after placement of a drug-eluting device in the vertebral artery (VA) origin, and describe management of restenosis with the stent-in-stent technique. Two women, one 62 and the other 67 years of age, underwent stent placement in the VA origin to treat symptomatic and angiographically significant stenosis in this vessel. Sirolimus-eluting coronary stents (Cypher) were used in both cases. Four months after placement of the devices, the symptoms recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…However, for patients with symptomatic fracture and restenosis, the stent-in-stent technique, as described by Kim et al, may be an option. 21 There are some limitations of this study. First, there may be a selection bias because of its retrospective nature.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, for patients with symptomatic fracture and restenosis, the stent-in-stent technique, as described by Kim et al, may be an option. 21 There are some limitations of this study. First, there may be a selection bias because of its retrospective nature.…”
Section: Discussionmentioning
confidence: 91%
“…Some authors have also reported stent fracture as a complication of ostial VA stenosis, and stent fracture rates range from 5% to 50%. 13,20,21 Weber et al reported two fractures (5%) associated with restenosis. However, during a mean followup of 31.5 months, Tsutsumi et al reported three stent fractures (50%) detected in coronary stents deployed for symptomatic ostial VA stenosis.…”
Section: Discussionmentioning
confidence: 96%
“…3,4 Endovascular treatment with balloon angioplasty alone yields unsatisfactory results due to elastic recoil, vessel dissection, and high restenosis rates. 5,6 Studies on stent placement of ostial vertebral artery lesions by using bare metal stents have reported excellent immediate results and low rates of periprocedural complications; however, mid-and longterm results remained disappointing due to issues of stent fracture caused by mechanical strain [7][8][9] and high rates of instent restenosis as a result of neointimal hyperplasia. 7,10,11 The use of drug-eluting coronary stents (DES) for the prevention of in-stent restenosis in ostial vertebral artery stenotic lesions has been advocated recently.…”
mentioning
confidence: 99%
“…Weber reported two stent fractures in his case series of 38 patients11; another study by Tsutsumi showed that three out of 12 patients had stent fractures and all were asymptomatic 13. There were two case reports of three patients with symptomatic stent fracture 12 14. The mechanism of ISR in stent fracture is probably related to higher mechanical irritation by the fractured struts causing smooth muscle proliferation and impaired re-endothelization.…”
Section: Discussionmentioning
confidence: 99%